Victim Precipitation and the Wage Gap. Issue 1 (6th March 2018) - Cheng, Shannon; Corrington, Abigail; Hebl, Mikki; Ng, Linnea; Watson, Ivy
Abstract : Cortina, Rabelo, and Holland (2018 ) accurately cite the general public's overuse of victim precipitation ideologies, or the notion that victims engage in actions that directly bring about their unfortunate circumstances. These ideologies also have permeated industrial and organizational (I-O) psychology and the study of people in the workplace (e.g., women's choice in clothing leads to sexual harassment, certain target characteristics and actions incite workplace bullying). We agree with Cortina et al. that this ideology unintentionally benefits the perpetrator by placing blame and responsibility for nonoptimal workplace situations directly on the target. The field of I-O psychology needs to move away from this model of victim blaming as a remediation for workplace disparities.